2011
DOI: 10.1007/s00167-011-1846-9
|View full text |Cite
|
Sign up to set email alerts
|

No effect on performance tests from a neuromuscular warm-up programme in youth female football: a randomised controlled trial

Abstract: Purpose The objective of the present randomised controlled trial was to study the effect of a neuromuscular warm-up programme on performance tests in youth female football.Methods Four youth female football teams with players aged 12-16 years were randomised into an intervention group and control group. The intervention was a 15-minute neuromuscular warm-up program carried out twice a week during the 11-week study period.Baseline and follow-up measurements of performance were made indoors and included the star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 19 publications
5
73
1
Order By: Relevance
“…However, contrary to the other neuromuscular control measures, the SEBT did not differ between the two groups with only a trend for higher values in the "FIFA 11+" group (P = 0.11). This finding appears to be in agreement with the study by Lindblom et al (2012) conducted on young female players which found no improvement in SEBT in the intervention group after a neuromuscular warm-up.…”
Section: Neuromuscular Measuressupporting
confidence: 92%
See 2 more Smart Citations
“…However, contrary to the other neuromuscular control measures, the SEBT did not differ between the two groups with only a trend for higher values in the "FIFA 11+" group (P = 0.11). This finding appears to be in agreement with the study by Lindblom et al (2012) conducted on young female players which found no improvement in SEBT in the intervention group after a neuromuscular warm-up.…”
Section: Neuromuscular Measuressupporting
confidence: 92%
“…However, during all these activities, particular attention should be devoted by the operators to the correct execution of the drills and therefore these exercises can be considered as additional neuromuscular training. Although previous studies have examined the effect on physical performance of prevention programmes and neuromuscular warm-up (Kilding et al, 2008;Lindblom, Walden, & Hagglund, 2012;Steffen et al, 2008;Vescovi & VanHeest, 2010), we did not expect substantial improvements in performance measures since the stimulus did not appear to be enough for inducing meaningful effects. As a consequence, we hypothesised to find improvement in neuromuscular control, which is also the main aim of the "FIFA 11+".…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…According to the different authors (10,22,31), women may be at higher risk of serious injury than men. The rate of cruciate ligaments injuries is three to five times higher among girls than among boys (10), which shows the importance of this kind of attention to the training of women athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The best result (m) of the three attempts was normalised to leg length (test value/leg length × 100). A composite score was calculated for each limb as the average of the three normalised measurements in the different directions [121]. The SEBT has high test re-test and inter-rater reliability (ICC, 0.82-0.98) [41,172].…”
Section: Functional Performance Testsmentioning
confidence: 99%